Incantational and Catechetical Style in Early Quaker Prose Writings - Roads, Judith (Quaker studies, 2014)
This article investigates two variants of early Quaker written style that have been noted in the literature: the ‘incantational’ style, so termed by Cope (1956), and the ‘catechetical’ style as defined by Bauman (1998). The inquiry confirms the existence of these two styles, gives examples of linguistic features of each and contrasts one variant with the other. Both styles are present in a number of the texts that comprise my digital Quaker corpus and from that evidence it is clear that writers chose in their persuasive discourse to employ features from these two distinct styles throughout the second half of the seventeenth century. The incantational style is less in evidence by the close of the century and the article puts forward reasons why that might be so.